All-solid-state battery, preparation method thereof and power utilization device

By using the melting and re-curing of halide solid electrolyte in an all-solid-state battery to form a continuous phase structure, the interface problem of solid-state batteries is solved, the internal resistance is reduced and the lithium ion conduction capacity is improved, and the performance and life of the battery are improved.

CN119324246APending Publication Date: 2025-01-17QINGTAO (KUNSHAN) ENERGY DEV CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411476419.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-22
Publication Date
2025-01-17

AI Technical Summary

Technical Problem

Due to interface problems caused by solid-state batteries, the internal resistance is increased, the available capacity is reduced, the circulation performance is deteriorated and the heat generation is severe, and the lithium ion transmission is poor, affecting the battery performance.

Method used

Using a composite positive electrode, a solid electrolyte layer and a composite negative electrode, the first halide solid electrolyte, the second halide solid electrolyte and the third halide solid electrolyte are converted from solid state to liquid state in the battery, and then from liquid state to solid state to form a continuous The phase structure improves the interface between the electrode and the solid electrolyte layer, reduces internal resistance and establishes a good lithium ion transmission channel.

Benefits of technology

Effectively reduce the internal resistance of all-solid-state batteries, improve rate performance and cycling performance, improve lithium ion conduction effect, and extend battery life.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119324246A_ABST
    Figure CN119324246A_ABST
Patent Text Reader

Abstract

The invention provides an all-solid-state battery, a preparation method thereof and a power utilization device. The all-solid-state battery comprises a composite positive electrode, a solid-state electrolyte layer and a composite negative electrode which are sequentially arranged, the composite positive electrode comprises a first halide solid-state electrolyte, the solid-state electrolyte layer comprises a second halide solid-state electrolyte, and the composite negative electrode comprises a third halide solid-state electrolyte. The first halide solid-state electrolyte, the second halide solid-state electrolyte and the third halide solid-state electrolyte are converted into liquid states from solid states in the battery and then converted into solid states from liquid states, and the first halide solid-state electrolyte and the second halide solid-state electrolyte form a continuous phase in the liquid states; and the third halide solid electrolyte and the second halide solid electrolyte form a continuous phase in a liquid state. And continuous conduction channels for lithium ions are formed between the composite positive electrode and the solid-state electrolyte layer and between the composite negative electrode and the solid-state electrolyte layer, so that the transmission capability for the lithium ions is improved, and the electrochemical performance of the all-solid-state battery is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of energy storage technology, and in particular to an all-solid-state battery and a preparation method and an electrical device thereof. Background Art

[0002] Solid-state batteries are energy storage elements that can store electrical energy and release it when needed. Compared with traditional liquid batteries, solid-state batteries use solid electrolytes instead of liquid or gel electrolytes for ion transmission, and have higher safety, higher energy density, faster charging speed and longer cycle life.

[0003] However, solid-state batteries still face some challenges in their full commercial use. The solid electrolyte layer and the positive and negative electrode layers are all solid layered structures. Compared with solid-liquid contact, solid-solid contact has more serious interface problems. On the one hand, it will lead to an increase in the internal resistance of the battery, resulting in a decrease in the available capacity of the battery, deterioration of the cycle performance, severe heat generation and other problems. On the other hand, due to the stacking properties, hardness and shape of the solid particles, the solid electrolyte cannot guarantee good lithium ion transmission inside the battery by relying solely on the contact between the solid particles, which seriously affects the performance of the battery. Summary of the invention

[0004] Based on this, it is necessary to provide an all-solid-state battery and its preparation method and electrical device that can reduce the internal resistance of the battery and improve the lithium ion conductivity.

[0005] In one aspect of the present application, an all-solid-state battery is provided, wherein the all-solid-state battery comprises a composite positive electrode, a solid electrolyte layer and a composite negative electrode arranged in sequence;

[0006] The composite positive electrode includes a first halide solid electrolyte;

[0007] The solid electrolyte layer includes a second halide solid electrolyte;

[0008] The composite negative electrode includes a third halide solid electrolyte;

[0009] The first halide solid electrolyte, the second halide solid electrolyte, and the third halide solid electrolyte are transformed from solid to liquid in the battery, and then transformed from liquid to solid;

[0010] Furthermore, the first halide solid electrolyte and the second halide solid electrolyte form a continuous phase in a liquid state, and the third halide solid electrolyte and the second halide solid electrolyte form a continuous phase in a liquid state.

[0011] In some embodiments, the melting points of the first halide solid electrolyte, the second halide solid electrolyte, and the third halide solid electrolyte are all 80° C. to 200° C.

[0012] In some embodiments, the difference in melting points among the first halide solid electrolyte, the second halide solid electrolyte, and the third halide solid electrolyte is ±20°C.

[0013] In some embodiments, the first halide solid electrolyte, the second halide solid electrolyte, and the third halide solid electrolyte are independently selected from Li3MCl 6-x Br x At least one of, wherein M is selected from Ga 3+ 、In 3+ 、Al 3+ , Fe 3+ , Y 3+ Sc 3+ 、Bi 3+ and one or more of trivalent lanthanide metal ions, 0 <x<6。

[0014] In some embodiments, 2≤x≤5.

[0015] In some embodiments, the first halide solid electrolyte, the second halide solid electrolyte, and the third halide solid electrolyte are of the same material.

[0016] In some embodiments, in the composite positive electrode, the mass proportion of the first halide solid electrolyte is 5% to 40%; and / or,

[0017] In the composite negative electrode, the mass proportion of the third halide solid electrolyte is 8% to 50%; and / or,

[0018] In the solid electrolyte layer, the mass proportion of the second halide solid electrolyte is 20% to 60%.

[0019] In some embodiments, the composite positive electrode and / or the composite negative electrode includes a stacked first electrode layer and a second electrode layer, the second electrode layer is arranged on a side of the first electrode layer close to the solid electrolyte layer; the second electrode layer is arranged on a side of the first electrode layer close to the solid electrolyte layer, and the mass proportion of the first halide solid electrolyte or the third halide solid electrolyte in the second electrode layer is greater than the mass proportion of the first halide solid electrolyte or the third halide solid electrolyte in the first electrode layer;

[0020] In some embodiments, in the composite positive electrode, the mass proportion of the first halide solid electrolyte in the second electrode layer is greater than the mass proportion of the first halide solid electrolyte in the first electrode layer;

[0021] In some embodiments, in the composite negative electrode, the mass proportion of the third halide solid electrolyte in the second electrode layer is greater than the mass proportion of the third halide solid electrolyte in the first electrode layer.

[0022] In some embodiments, the composite positive electrode includes a stacked first pole layer and a second pole layer, the second pole layer is arranged on a side of the first base layer close to the solid electrolyte layer, and in the composite positive electrode, the second pole layer includes a first halide solid electrolyte; the first pole layer does not include the first halide solid electrolyte.

[0023] In some embodiments, the composite negative electrode includes a first electrode layer and a second electrode layer stacked, the second electrode layer is arranged on a side of the first base layer close to the solid electrolyte layer, and in the composite negative electrode, the second electrode layer includes a third halide solid electrolyte; the first electrode layer does not include the third halide solid electrolyte. In some embodiments, there are multiple second electrode layers, and the multiple second electrode layers are located between the first electrode layer and the solid electrolyte layer; wherein, along the direction close to the solid electrolyte layer, the content of the first halide solid electrolyte in the multiple second electrode layers increases successively; and / or, the content of the third halide solid electrolyte in the multiple second electrode layers increases successively.

[0024] Another aspect of the present application provides a method for preparing an all-solid-state battery, the method comprising:

[0025] Prepare a battery structure: prepare a composite positive electrode, a solid electrolyte layer, and a composite negative electrode respectively and stack them to form a battery structure; the composite positive electrode includes a first halide solid electrolyte, the solid electrolyte layer includes a second halide solid electrolyte, and the composite negative electrode includes a third halide solid electrolyte;

[0026] The battery structure is subjected to hot pressing treatment to obtain an all-solid-state battery; wherein the first halide solid electrolyte, the second halide solid electrolyte, and the third halide solid electrolyte are transformed from a solid state to a liquid state in the battery, and then transformed from a liquid state to a solid state, and the first halide solid electrolyte and the second halide solid electrolyte form a continuous phase in the liquid state, and the third halide solid electrolyte and the second halide solid electrolyte form a continuous phase in the liquid state.

[0027] In some embodiments, the melting points of the first halide solid electrolyte, the second halide solid electrolyte, and the third halide solid electrolyte are 80° C. to 200° C.; and / or

[0028] The temperature of the hot pressing treatment is 80°C to 220°C; and / or,

[0029] The heat pressing treatment time is 3min to 20min; and / or,

[0030] The pressure of the hot pressing treatment is 10MPa~500MPa.

[0031] In some embodiments, the temperature of the hot pressing treatment is greater than or equal to the maximum value of the melting points of the first halide solid electrolyte, the second halide solid electrolyte, and the third halide solid electrolyte.

[0032] Another aspect of the present application provides an electrical device comprising the all-solid-state battery as described above.

[0033] In the above-mentioned all-solid-state battery, the composite positive electrode, the solid electrolyte layer and the composite negative electrode include a first halide solid electrolyte, a second halide solid electrolyte and a third halide solid electrolyte. The first halide solid electrolyte, the second halide solid electrolyte and the third halide solid electrolyte are melted from a solid state to a liquid state in the battery, and then transformed from a liquid state to a solid state. The liquid halide solid electrolyte can penetrate into various places in the active layer and flow to the interface between the electrode and the solid electrolyte layer to form a continuous structure, thereby improving the poor interface between the electrode and the solid electrolyte layer due to solid-solid contact, and effectively reducing the internal resistance of the all-solid-state battery. At the same time, a good lithium ion transmission channel is established inside the all-solid-state battery, which is beneficial to the improvement of the rate performance of the all-solid-state battery. BRIEF DESCRIPTION OF THE DRAWINGS

[0034] FIG1 is a schematic diagram of a method for preparing an all-solid-state battery according to one embodiment. DETAILED DESCRIPTION

[0035] References to embodiments of the present application will now be provided in detail, one or more examples of which are described below. Each example is provided as an explanation rather than a limitation of the present application. In fact, it will be apparent to those skilled in the art that various modifications and variations may be made to the present application without departing from the scope or spirit of the present application. For example, a feature described or described as part of one embodiment may be used in another embodiment to produce a further embodiment.

[0036] Therefore, it is intended that the present application covers such modifications and variations that fall within the scope of the appended claims and their equivalents. Other objects, features and aspects of the present application are disclosed in or are apparent from the following detailed description. It will be appreciated by those of ordinary skill in the art that this discussion is merely a description of exemplary embodiments and is not intended to limit the broader aspects of the present application.

[0037] In the present application, the technical features described in an open manner include closed technical solutions composed of the listed features, and also include open technical solutions containing the listed features.

[0038] In the present application, when it comes to numerical ranges, unless otherwise specified, the above numerical ranges are deemed to be continuous and include the minimum and maximum values ​​of the range, as well as each value between such minimum and maximum values. Further, when a range refers to an integer, each integer between the minimum and maximum values ​​of the range is included. In addition, when multiple ranges are provided to describe features or characteristics, the ranges can be merged. In other words, unless otherwise specified, all ranges disclosed herein should be understood to include any and all sub-ranges included therein. If not otherwise specified, all embodiments and optional embodiments of the present application can be combined with each other to form a new technical solution.

[0039] Unless otherwise specified, all technical features and optional technical features of this application can be combined with each other to form a new technical solution.

[0040] If there is no special explanation, all the steps of the present application can be performed sequentially or randomly, preferably sequentially.

[0041] For example, the method includes steps S12 and S14, which means that the method may include steps S12 and S14 performed sequentially, or may include steps S14 and S12 performed sequentially. For example, mentioning that the method may also include step S16 means that step S16 may be added to the method in any order, for example, the method may include steps S12, S14 and S16, or may include steps S12, S16 and S14, or may include steps S16, S12 and S14, etc.

[0042] If there is no special explanation, the "include" and "comprising" mentioned in this application are open-ended or closed-ended. For example, the "include" and "comprising" may mean that other components not listed may also be included or only the listed components may be included or only the listed components may be included.

[0043] If not specifically stated, in this application, the term "or" is inclusive. For example, the phrase "A or B" means "A, B, or both A and B". More specifically, any of the following conditions satisfies the condition "A or B": A is true (or exists) and B is false (or does not exist); A is false (or does not exist) and B is true (or exists); or both A and B are true (or exist).

[0044] In all-solid-state batteries, the solid electrolyte membrane plays the role of conducting lithium ions. There are interface problems when the positive electrode, negative electrode and solid electrolyte membrane contact each other. The existing interface is affected by the positive electrode material or the negative electrode material, and it is difficult to make the surface completely flat, resulting in a decrease in the lithium ion conduction effect.

[0045] Solid electrolytes have no flow properties and cannot infiltrate the positive and negative electrodes, resulting in poor contact between the solid electrolyte and the positive and negative electrodes. Traditional technology incorporates solid electrolyte particles and other lithium ion conductive materials into the positive electrode, which to a certain extent solves the lithium ion conduction inside the electrode. However, the lithium ion conduction of solid electrolytes relies on solid-phase contact conduction, and the lithium ion conduction efficiency of granular solid electrolytes is limited, which is not conducive to improving the performance of all-solid-state batteries.

[0046] In one aspect of the present application, an all-solid-state battery is provided, comprising a composite positive electrode, a solid electrolyte layer and a composite negative electrode arranged in sequence, the composite positive electrode comprising a first halide solid electrolyte, the solid electrolyte layer comprising a second halide solid electrolyte, the composite negative electrode comprising a third halide solid electrolyte, the first halide solid electrolyte, the second halide solid electrolyte and the third halide solid electrolyte being transformed from a solid state to a liquid state and then transformed from a liquid state to a solid state in the battery, and the first halide solid electrolyte and the second halide solid electrolyte forming a continuous phase in the liquid state, and the third halide solid electrolyte and the second halide solid electrolyte forming a continuous phase in the liquid state.

[0047] In the all-solid-state battery, the first halide solid electrolyte, the second halide solid electrolyte, and the third halide solid electrolyte can all be transformed from solid to liquid in the battery, and then transformed from liquid to solid. When the first halide solid electrolyte, the second halide solid electrolyte, and the third halide solid electrolyte are all liquid, the liquid halide solid electrolyte can penetrate into various parts of the active layer and flow to the interface between the electrode and the solid electrolyte layer to form a continuous structure, thereby improving the poor interface between the electrode and the solid electrolyte layer due to solid-solid contact, and effectively reducing the internal resistance of the all-solid-state battery. At the same time, a good lithium ion transmission channel is established inside the all-solid-state battery, which is beneficial to the improvement of the rate performance of the all-solid-state battery.

[0048] In some embodiments, the melting points of the first halide solid electrolyte, the second halide solid electrolyte, and the third halide solid electrolyte are all 80° C. to 200° C. The melting point temperature may be, but is not limited to, 80° C., 100° C., 120° C., 140° C., 150° C., 160° C., 180° C., 200° C., etc. Thus, reaching the melting point temperature during heat treatment can transform the first halide solid electrolyte, the second halide solid electrolyte, and the third halide solid electrolyte from solid to liquid.

[0049] In some embodiments, the ionic conductivity λ of the first halide solid electrolyte, the second halide solid electrolyte, and the third halide solid electrolyte satisfies λ≥1 mS / cm; preferably, λ≥1.5 mS / cm, and more preferably, λ≥2 mS / cm.

[0050] In some embodiments, the difference in melting points of the first halide solid electrolyte, the second halide solid electrolyte, and the third halide solid electrolyte is ±20° C. The difference between the highest melting point temperature and the lowest melting point temperature of the first halide solid electrolyte, the second halide solid electrolyte, and the third halide solid electrolyte is within a range of 20° C., including 20° C.

[0051] In some embodiments, the first halide solid electrolyte, the second halide solid electrolyte, and the third halide solid electrolyte are independently selected from Li3MCl 6-x Br x At least one of, wherein M is selected from Ga 3+ 、In 3+ 、Al 3+ , Fe 3+ , Y 3+ Sc 3+ 、Bi 3+ and one or more trivalent lanthanide metals, 0 <x<6。

[0052] In some preferred embodiments, M is selected from Ga 3+ 、In 3+ 、Al 3+ , Fe 3+ , Y 3+ Sc 3+ 、Bi 3+ , one or more of trivalent lanthanide metals, and the value range of x is 2≤x≤5. For example, Li3MCl 6-x Br x It can be but not limited to Li3Y 0.5 Dy 0.5 Cl3Br3、Li3In 0.5 Fe 0.5 Cl3Br3, Li3YCl3Br3.

[0053] In some embodiments, the first halide solid electrolyte, the second halide solid electrolyte, and the third halide solid electrolyte are of the same material.

[0054] In some embodiments, in the composite positive electrode, the mass proportion of the first halide solid electrolyte is 5% to 40%. Exemplarily, the mass proportion of the first halide solid electrolyte in the composite positive electrode can be but not limited to 5%, 10%, 15%, 20%, 25%, 30%, 35% or 40%, etc. The composite positive electrode also includes a positive electrode active material, and the first halide solid electrolyte has a good ratio at the above content, ensuring the content of the positive electrode active material.

[0055] In some embodiments, in the composite negative electrode, the mass proportion of the third halide solid electrolyte is 8% to 50%. Exemplarily, the mass proportion of the third halide solid electrolyte in the composite positive electrode can be, but is not limited to, 8%, 10%, 15%, 20%, 25%, 30%, 35%, 40%, 45% or 50%, etc. The composite negative electrode also includes a negative electrode active material, and the third halide solid electrolyte has a good ratio at the above content, ensuring the content of the negative electrode active material.

[0056] In some embodiments, in the solid electrolyte layer, the mass proportion of the second halide solid electrolyte is 20% to 60%. Exemplarily, the mass proportion of the second halide solid electrolyte in the solid electrolyte layer may be, but is not limited to, 20%, 25%, 30%, 35%, 40%, 45%, 50%, 55% or 60%, etc. The solid electrolyte layer may also include other solid electrolytes.

[0057] In some embodiments, the composite positive electrode and / or the composite negative electrode includes a stacked first pole layer and a second pole layer, the second pole layer is arranged on a side of the first pole layer close to the solid electrolyte layer, and the mass proportion of the first halide solid electrolyte or the third halide solid electrolyte in the second pole layer is greater than the mass proportion of the first halide solid electrolyte or the third halide solid electrolyte in the first pole layer.

[0058] In some embodiments, in the composite positive electrode, the mass proportion of the first halide solid electrolyte in the second electrode layer is greater than the mass proportion of the first halide solid electrolyte in the first electrode layer.

[0059] In some embodiments, in the composite negative electrode, the mass proportion of the third halide solid electrolyte in the second electrode layer is greater than the mass proportion of the third halide solid electrolyte in the first electrode layer.

[0060] In some embodiments, the composite positive electrode includes a stacked first pole layer and a second pole layer, the second pole layer is arranged on a side of the first base layer close to the solid electrolyte layer, and in the composite positive electrode, the second pole layer includes a first halide solid electrolyte; the first pole layer does not include the first halide solid electrolyte.

[0061] In some embodiments, the composite negative electrode includes a stacked first electrode layer and a second electrode layer, the second electrode layer is arranged on a side of the first base layer close to the solid electrolyte layer, and in the composite negative electrode, the second electrode layer includes a third halide solid electrolyte; the first electrode layer does not include a third halide solid electrolyte.

[0062] In some embodiments, there are multiple second pole layers, and the multiple second pole layers are located between the first pole layer and the solid electrolyte layer; wherein, along the direction close to the solid electrolyte layer, the content of the first halide solid electrolyte in the multiple second pole layers increases successively. In some embodiments, along the direction close to the solid electrolyte layer, the content of the third halide solid electrolyte in the multiple second pole layers increases successively. It is distributed in a gradient in the composite positive electrode / composite negative electrode, with a higher content on the side close to the solid electrolyte layer, ensuring the conduction of lithium ions, and a lower content on the side away from the solid electrolyte layer, which increases the proportion of the active material content and ensures the active material content.

[0063] In addition, during the hot pressing process, the solid electrolyte flows in multiple second electrode layers to form a stepped distribution, that is, the content of the solid electrolyte increases in the direction close to the solid electrolyte membrane, so that the lithium ion conduction channel is continuous.

[0064] In a second aspect, as shown in FIG1 , the present application further provides a method for preparing an all-solid-state battery, the method comprising the following steps:

[0065] S1, preparing a battery structure: preparing a composite positive electrode, a solid electrolyte layer, and a composite negative electrode respectively and stacking them to form a battery structure, the composite positive electrode includes a first halide solid electrolyte, the solid electrolyte layer includes a second halide solid electrolyte, and the composite negative electrode includes a third halide solid electrolyte.

[0066] S2, performing hot pressing treatment on the battery structure to obtain an all-solid-state battery, wherein the first halide solid electrolyte, the second halide solid electrolyte, and the third halide solid electrolyte are transformed from a solid state to a liquid state in the battery, and then transformed from a liquid state to a solid state, and the first halide solid electrolyte and the second halide solid electrolyte form a continuous phase in the liquid state, and the third halide solid electrolyte and the second halide solid electrolyte form a continuous phase in the liquid state.

[0067] In some embodiments, the melting points of the first halide solid electrolyte, the second halide solid electrolyte, and the third halide solid electrolyte are 80°C to 200°C.

[0068] In some embodiments, the temperature of the hot pressing treatment is greater than or equal to the maximum value of the melting points of the first halide solid electrolyte, the second halide solid electrolyte, and the third halide solid electrolyte.

[0069] In some embodiments, the temperature of the hot pressing treatment is 80°C to 220°C, including but not limited to 80°C, 100°C, 120°C, 140°C, 150°C, 160°C, 180°C, 200°C or 220°C. In this way, the first halide solid electrolyte, the second halide solid electrolyte, and the third halide solid electrolyte can be ensured to have a certain fluidity during the hot pressing treatment, and the binder in the pole piece will not be excessively melted. Further, the temperature of the hot pressing treatment can be 80~200°C.

[0070] In some embodiments, the time of hot pressing treatment is 3min~20min, including but not limited to 3min, 4min, 5min, 6min, 8min, 10min, 12min, 14min, 15min, 16min, 18min or 20min, etc. In this way, the first halide solid electrolyte, the second halide solid electrolyte, and the third halide solid electrolyte can flow within a certain time, have a suitable flow range, and will not cause excessive loss of the solid electrolyte layer when they can flow to the interface between the pole piece and the solid electrolyte layer, thereby ensuring the conductivity of lithium ions. Further, the time of hot pressing treatment can be 5min-15min.

[0071] In some embodiments, the pressure of the hot pressing treatment is 10MPa~500MPa, including but not limited to 10MPa, 20MPa, 50MPa, 80MPa, 100MPa, 150MPa, 200MPa, 250MPa, 300MPa, 350MPa, 400MPa, 450MPa or 500MPa, etc. In this way, the hot pressing pressure can promote the flow of the first halide solid electrolyte, the second halide solid electrolyte, and the third halide solid electrolyte within a suitable range without damaging the pole piece and the solid electrolyte layer structure. Further, the pressure of the hot pressing treatment can be 50MPa~250MPa.

[0072] In a third aspect, the present application also provides an electrical device, comprising the all-solid-state battery in any of the above embodiments.

[0073] The following are specific embodiments.

[0074] Example 1

[0075] (1) Preparation of battery structure

[0076] ① Preparation of positive electrode: NCM811, PTFE, super-P, and the first halide solid electrolyte Li3YCl3Br3 are uniformly mixed in a mass ratio of 70:3:2:25, put into a high shear force equipment mixer, and subjected to fiberization treatment to form a first mixture, and the first mixture is rolled to form a first positive electrode layer; the rolling temperature is 60°C, and the rolling time is 5 minutes;

[0077] ② Preparation of negative electrode: The negative electrode active material graphite, (CMC+SBR), super-P and the second halide solid electrolyte Li3YCl3Br3 are mixed evenly in a mass ratio of 69:4:2:25, put into a high shear force equipment mixer, and subjected to fiberization treatment to form a second mixture, and the second mixture is rolled to form a first negative electrode layer; the rolling temperature is 60°C, and the rolling time is 5 minutes;

[0078] ③ Preparation of solid electrolyte membrane: The halide solid electrolyte Li2ZrCl6, the third halide solid electrolyte Li3YCl3Br3 and the binder PTFE are mixed in a mass ratio of 62:35:3, and then pressed into a membrane;

[0079] ④Battery structure preparation

[0080] The positive electrode current collector, the positive electrode layer, the solid electrolyte membrane, the negative electrode layer and the negative electrode current collector are stacked to obtain a battery structure.

[0081] (2) Hot pressing treatment

[0082] The battery structure is subjected to hot pressing treatment to form an all-solid-state battery, wherein the hot pressing temperature is 130°C, the hot pressing time is 12 minutes, and the hot pressing pressure is 200 MPa.

[0083] Among them, the melting point of Li3YCl3Br3 is 115℃.

[0084] Example 2

[0085] (1) Preparation of battery structure

[0086] ① Preparation of positive electrode: NCM811, PTFE, super-P, and the first halide solid electrolyte Li3YCl3Br3 are uniformly mixed in a mass ratio of 70:3:2:25, put into a high shear force equipment mixer, and subjected to fiberization treatment to form a first mixture, and the first mixture is rolled to form a first positive electrode layer; the rolling temperature is 60°C, and the rolling time is 5 minutes;

[0087] ② Preparation of negative electrode: negative electrode active materials graphite, (CMC+SBR), super-P and second halide solid electrolyte Li3In 0.5 Fe 0.5 Cl3Br3 is mixed uniformly in a mass ratio of 69:4:2:25, put into a high shear force equipment mixer, and subjected to fiberization treatment to form a second mixture, which is then rolled to form a first negative electrode layer; the rolling temperature is 60° C., and the rolling time is 5 min;

[0088] ③ Preparation of solid electrolyte membrane: Halide solid electrolyte Li2ZrCl6, third halide solid electrolyte Li3Y 0.5 Dy 0.5 Cl3Br3 and binder PTFE were mixed in a mass ratio of 62:35:3 and then pressed into a film;

[0089] ④Battery structure preparation

[0090] The positive electrode current collector, the positive electrode layer, the solid electrolyte membrane, the negative electrode layer and the negative electrode current collector are stacked to obtain a battery structure.

[0091] (2) Hot pressing treatment

[0092] The battery structure is subjected to hot pressing treatment to form an all-solid-state battery, wherein the hot pressing temperature is 130°C, the hot pressing time is 12 minutes, and the hot pressing pressure is 100 MPa.

[0093] Among them, the melting point of Li3YCl3Br3 is 115℃, Li3In 0.5 Fe 0.5 The melting point of Cl3Br3 is 125℃, Li3Y 0.5 Dy 0.5 The melting point of Cl3Br3 is 120℃.

[0094] Example 3

[0095] (1) Prepare battery structure.

[0096] Preparation of composite positive electrode:

[0097] Prepare the first positive electrode layer, mix NCM811, PVDF, super-P and the first halide solid electrolyte Li3YCl3Br3 in a mass ratio of 80:3:2:15, put them into a high shear force equipment mixer, perform fiberization treatment to form a first mixture, and roll the first mixture to form a first positive electrode layer; the rolling temperature is 60°C, and the rolling time is 5 minutes;

[0098] The second positive electrode layer was prepared by uniformly mixing NCM811, PVDF, super-P and the first halide solid electrolyte Li3YCl3Br3 in a mass ratio of 70:3:2:25, placing the mixture in a high shear force equipment mixer, performing a fiberization treatment to form a first mixture, and rolling the first mixture to form a first positive electrode layer; the rolling temperature was 60°C, and the rolling time was 5 minutes;

[0099] Preparation of composite negative electrode:

[0100] Prepare the first negative electrode layer, mix the negative electrode active material graphite, (CMC+SBR), super-P and the second halide solid electrolyte Li3YCl3Br3 in a mass ratio of 75:4:2:19, put them into a high shear force equipment mixer, perform fiberization treatment to form a second mixture, and roll the second mixture to form the first negative electrode layer; the rolling temperature is 60°C, and the rolling time is 5 minutes;

[0101] Prepare the second negative electrode layer, mix the negative electrode active material graphite, (CMC+SBR), super-P and the second halide solid electrolyte Li3YCl3Br3 in a mass ratio of 69:4:2:25, put them into a high shear force equipment mixer, perform fiberization treatment to form a second mixture, and roll the second mixture to form the first negative electrode layer; the rolling temperature is 60°C, and the rolling time is 5 minutes;

[0102] Preparation of the solid electrolyte layer: The first halide solid electrolyte Li2ZrCl6, the second halide solid electrolyte Li3YCl3Br3 and the binder PTFE are mixed in a mass ratio of 62:35:3, and then pressed into a film.

[0103] ④Battery structure preparation

[0104] The positive electrode current collector, the positive electrode layer, the solid electrolyte membrane, the negative electrode layer and the negative electrode current collector are stacked to obtain a battery structure.

[0105] (2) Hot pressing treatment

[0106] The battery structure is subjected to hot pressing treatment to form an all-solid-state battery, wherein the hot pressing temperature is 130°C, the hot pressing time is 12 minutes, and the hot pressing pressure is 100 MPa.

[0107] Example 4

[0108] The preparation method of Example 4 is substantially the same as that of Example 1, except that:

[0109] The temperature of the hot pressing treatment is 160°C, the time is 2 min, and the pressure is 600 MPa.

[0110] Example 5

[0111] The preparation method of Example 5 is substantially the same as that of Example 1, except that:

[0112] The temperature of the hot pressing treatment is 115°C, the time is 20 min, and the pressure is 100 MPa.

[0113] Example 6

[0114] The preparation method of Example 6 is substantially the same as that of Example 1, except that:

[0115] The temperature of the hot pressing treatment is 140°C, the time is 3 min, and the pressure is 500 MPa.

[0116] Example 7

[0117] The preparation method of Example 7 is substantially the same as that of Example 1, except that:

[0118] In step ①, the mass ratio of NCM811, PTFE, super-P, and the first halide solid electrolyte Li3YCl3Br3 is 90:3:2:5;

[0119] In step ②, the negative electrode active material graphite, (CMC+SBR), super-P and the second halide solid electrolyte Li3YCl3Br3 are in the ratio of 86:4:2:8;

[0120] In step ③, the first halide solid electrolyte Li2ZrCl6, the second halide solid electrolyte Li3YCl3Br3 and the binder PTFE are mixed in a mass ratio of 37:60:3 and then pressed into a film.

[0121] Example 8

[0122] The preparation method of Example 8 is substantially the same as that of Example 1, except that:

[0123] In step ①, the mass ratio of NCM811, PTFE, super-P, and the first halide solid electrolyte Li3YCl3Br3 is 55:3:2:40;

[0124] In step ②, the negative electrode active material graphite, (CMC+SBR), super-P and the second halide solid electrolyte Li3YCl3Br3 are in the ratio of 44:4:2:50;

[0125] In step ③, the first halide solid electrolyte Li2ZrCl6, the second halide solid electrolyte Li3YCl3Br3 and the binder PTFE are mixed in a mass ratio of 77:20:3 and then pressed into a film.

[0126] Example 9

[0127] The preparation method of Example 9 is substantially the same as that of Example 1, except that:

[0128] In step ③, the first halide solid electrolyte Li2ZrCl6, the second halide solid electrolyte Li3YCl3Br3 and the binder PTFE are mixed in a mass ratio of 34.5:65:0.5, and then pressed into a film.

[0129] Comparative Example 1

[0130] The preparation method of Comparative Example 1 is substantially the same as that of Example 1, except that:

[0131] The first halide solid electrolyte, the second halide solid electrolyte, and the third halide solid electrolyte are replaced with Li2ZrCl6;

[0132] Comparative Example 2

[0133] The preparation method of Comparative Example 2 is substantially the same as that of Example 1, except that:

[0134] The hot pressing treatment replaced the normal temperature pressing, and the pressing temperature was 45°C.

[0135] The process parameters of the preparation methods of Examples 1 to 9 and Comparative Examples 1 to 2 are listed in Table 1 below:

[0136] Table 1

[0137]

[0138] The all-solid-state batteries prepared in Examples 1 to 9 and Comparative Examples 1 to 2 were subjected to performance tests, and the test results are shown in Table 2 below.

[0139] Among them, the test conditions or test standards for each performance test item are:

[0140] Battery performance test

[0141] ①Battery internal resistance test

[0142] At 25° C., the internal resistance of the all-solid-state lithium batteries in the embodiment and the comparative example was measured using a voltage internal resistance meter. The test results are shown in Table 2.

[0143] ②Cyclic performance test

[0144] The all-solid-state lithium batteries in the embodiments and comparative examples were subjected to a cycle test. At a temperature of 25°C±2°C, in the first step, they were charged at 0.1C to a final voltage of 4.5V, a cutoff current of 0.05C, and allowed to stand for 30 minutes; in the second step, they were discharged at 0.1C to a final discharge voltage of 2.7V, the discharge capacity was recorded, and the batteries were allowed to stand for 30 minutes; the first and second steps were repeated to test the cycle performance of the battery for 500 cycles.

[0145] ③Rate performance test

[0146] The battery was placed at 25°C for 10 min, then charged to 4.5 V at a constant current rate of 0.33C, placed for 10 min, and then discharged to 2.7 V at a constant current rate of 0.33C.

[0147] Charge at a constant current of 2C to 4.5V, leave for 10min, and then discharge at a constant current of 2C to 2.7V.

[0148] And calculate the capacity retention rate = 2C discharge capacity / 0.33C rate discharge capacity*100%.

[0149] Table 2

[0150]

[0151] As can be seen from Table 2 above, the first halide solid electrolyte, the second halide solid electrolyte, and the third halide solid electrolyte are added to the composite positive electrode, the solid electrolyte layer, and the composite negative electrode, respectively. During the hot pressing process, the first halide solid electrolyte, the second halide solid electrolyte, and the third halide solid electrolyte are melted. Under the action of pressure, a continuous phase is formed between the first halide solid electrolyte and the second halide solid electrolyte, and the third halide solid electrolyte forms a continuous phase with the second halide solid electrolyte. On the one hand, the internal resistance of the battery can be effectively reduced. On the other hand, a continuous conduction channel for lithium ions is established inside the battery to improve the transmission capacity of lithium ions, so as to improve the rate performance of the all-solid-state battery. In addition, the process of melting and then solidifying the first halide solid electrolyte, the second halide solid electrolyte, and the third halide solid electrolyte is conducive to forming a dense structure, which is conducive to preventing the formation and growth of lithium dendrites and improving the cycle performance of the all-solid-state battery.

[0152] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.

[0153] The above-described embodiments only express several implementation methods of the present application, and the descriptions thereof are relatively specific and detailed, but they cannot be construed as limiting the scope of the patent application. It should be pointed out that, for a person of ordinary skill in the art, several variations and improvements can be made without departing from the concept of the present application, and these all belong to the protection scope of the present application. Therefore, the protection scope of the patent application shall be subject to the attached claims.

Claims

1. An all-solid-state battery, characterized in that: The all-solid-state battery includes a composite positive electrode, a solid electrolyte layer and a composite negative electrode arranged in sequence, the composite positive electrode includes a first halide solid electrolyte, the solid electrolyte layer includes a second halide solid electrolyte, the composite negative electrode includes a third halide solid electrolyte, the first halide solid electrolyte, the second halide solid electrolyte, and the third halide solid electrolyte are transformed from a solid state to a liquid state in the battery, and then transformed from a liquid state to a solid state, and the first halide solid electrolyte and the second halide solid electrolyte form a continuous phase in a liquid state, and the third halide solid electrolyte and the second halide solid electrolyte form a continuous phase in a liquid state.

2. The all-solid-state battery according to claim 1, characterized in that: The melting points of the first halide solid electrolyte, the second halide solid electrolyte, and the third halide solid electrolyte are all 80° C. to 200° C.

3. The all-solid-state battery according to claim 1, characterized in that: The difference in melting points among the first halide solid electrolyte, the second halide solid electrolyte, and the third halide solid electrolyte is ±20°C.

4. The all-solid-state battery according to claim 1, characterized in that: The first halide solid electrolyte, the second halide solid electrolyte, and the third halide solid electrolyte are independently selected from Li3MCl 6-x Br x At least one of, wherein M is selected from Ga 3+ 、In 3+ 、Al 3+ , Fe 3+ , Y 3+ Sc 3+ 、Bi 3+ and one or more trivalent lanthanide metals, 0 <x<6。 5. The all-solid-state battery according to claim 4, characterized in that: The first halide solid electrolyte, the second halide solid electrolyte, and the third halide solid electrolyte are of the same material.

6. The all-solid-state battery according to claim 1, characterized in that: In the composite positive electrode, the mass proportion of the first halide solid electrolyte is 5% to 40%; and / or, In the composite negative electrode, the mass proportion of the third halide solid electrolyte is 8% to 50%; and / or, In the solid electrolyte layer, the mass proportion of the second halide solid electrolyte is 20% to 60%.

7. The all-solid-state battery according to claim 1, characterized in that: The composite positive electrode and / or the composite negative electrode comprises a first electrode layer and a second electrode layer stacked together, the second electrode layer is arranged on a side of the first electrode layer close to the solid electrolyte layer, and the mass proportion of the first halide solid electrolyte or the third halide solid electrolyte in the second electrode layer is greater than the mass proportion of the first halide solid electrolyte or the third halide solid electrolyte in the first electrode layer; Preferably, there are multiple second pole layers, and the multiple second pole layers are located between the first pole layer and the solid electrolyte layer; wherein, along the direction approaching the solid electrolyte layer, the content of the first halide solid electrolyte in the multiple second pole layers increases successively; and / or the content of the third halide solid electrolyte increases successively.

8. A method for preparing an all-solid-state battery, characterized in that: The preparation method comprises: Prepare a battery structure: prepare a composite positive electrode, a solid electrolyte layer, and a composite negative electrode respectively and stack them to form a battery structure; the composite positive electrode includes a first halide solid electrolyte, the solid electrolyte layer includes a second halide solid electrolyte, and the composite negative electrode includes a third halide solid electrolyte; The battery structure is subjected to hot pressing treatment to obtain an all-solid-state battery; wherein the first halide solid electrolyte, the second halide solid electrolyte, and the third halide solid electrolyte are transformed from a solid state to a liquid state in the battery, and then transformed from a liquid state to a solid state, and the first halide solid electrolyte and the second halide solid electrolyte form a continuous phase in the liquid state, and the third halide solid electrolyte and the second halide solid electrolyte form a continuous phase in the liquid state.

9. The preparation method according to claim 8, characterized in that: The melting points of the first halide solid electrolyte, the second halide solid electrolyte and the third halide solid electrolyte are 80° C. to 200° C.; and / or, The temperature of the hot pressing treatment is 80°C to 220°C; and / or, The heat pressing treatment time is 3min to 20min; and / or, The pressure of the hot pressing treatment is 10MPa~500MPa.

10. An electrical device, characterized in that: Comprising an all-solid-state battery as described in any one of claims 1 to 7.